Meningkatkan Kemampuan Menyusun Modul Ajar Terdiferensiasi melalui Bimbingan dan Pendampingan bagi Guru-Guru Pendidikan Pancasila dan IPS SMP Binaan F Semarang Tahun 2022 - Santosa, Slamet (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
The ability of civics and social studies teachers at Assisted F Middle School Semarang City in compiling differentiated teaching modules has not been optimal. Before the guidance and assistance, the average ability was 53%. The research procedure used in this study is School Action Research. The procedure or steps are carried out through 2 cycles of action. The results in cycle I averaged the ability to compile differentiated teaching modules, increased by 12% from 53% increased to 65%. There were 63.3% of civics teachers and social studies teachers at Assisted F Junior High Schools who experienced an increase in the ability of the good category in compiling teaching modules dedifferentiation. The average level of enjoyment (student wellbeing) of civics teachers and Social Studies teachers F reached 67%. The average ability to compile teaching modules in cycle II increased by 12% from 65% to 78%, including the good category. There are 83.3% of civics and social studies teachers who have good abilities in compiling differentiated teaching modules, including the good category. Guidance and assistance through workshops, mentoring guidance to small groups and individuals running smoothly can improve the ability and motivation of civic and social studies teachers at Assisted F Middle School Semarang City. in compiling differentiated teaching modules.